The Impact Of Air Quality On Respiratory Health in Urban Populations - Dimas Widodo; Rani Arifin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research examines the relationship between air quality and respiratory health in urban populations. By analyzing data on air pollution levels and health outcomes such as asthma and chronic obstructive pulmonary disease (COPD), the study identifies significant correlations between poor air quality and increased respiratory issues. The findings underscore the need for policy changes aimed at improving air quality to enhance public health in urban settings.